Evidence supporting see‐and‐treat management of cervical intraepithelial neoplasia: a systematic review and meta‐analysis - Ebisch, RMF; Rovers, MM; Bosgraaf, RP; Pluijm‐Schouten, HW; Melchers, WJG; Akker, PAJ; Massuger, LFAG; Bekkers, RLM (BJOG : an international journal of obstetrics and gynaecology, 2016)
Background Studies of see‐and‐treat management of cervical intraepithelial neoplasia (CIN) vary in their inclusion criteria, resulting in a broad range of overtreatment rates. Objectives To determine overtreatment rates in see‐and‐treat management of women referred for colposcopy because of suspected CIN, in order to define circumstances supporting see‐and‐treat management. Search strategy MEDLINE, EMBASE, and the Cochrane Library were searched from inception up to 12 May 2014. Selection criteria Studies of see‐and‐treat management in women with a reported cervical smear result, colposcopic impression, and histology result were included. Data collection and analysis Methodological quality was assessed with the Newcastle–Ottawa scale. We used the inverse variance method for pooling incidences, and a random‐effects model was used to account for heterogeneity between studies. Overtreatment was defined as treatment in patients with no CIN or CIN1. Main results Thirteen studies (n = 4611) were included. The overall overtreatment rate in women with a high‐grade cervical smear and a high‐grade colposcopic impression was 11.6% (95% CI 7.8–15.3%). The overtreatment rate in women with a high‐grade cervical smear and low‐grade colposcopic impression was 29.3% (95% CI 16.7–41.9%), and in the case of a low‐grade smear and high‐grade colposcopic impression it was 46.4% (95% CI 15.7–77.1%). In women with a low‐grade smear and low‐grade colposcopic impression, the overtreatment rate was 72.9% (95% CI 68.1–77.7%). Author's conclusions The pooled overtreatment rate in women with a high‐grade smear and high‐grade colposcopic impression is at least comparable with the two‐step procedure, which supports the use of see‐and‐treat management in this subgroup of women. Tweetable See‐and‐treat management is justified in the case of a high‐grade smear and a high‐grade colposcopic impression. Tweetable See‐and‐treat management is justified in the case of a high‐grade smear and a high‐grade colposcopic impression.